Perceptions of the Cardiologists and Oncologists: Initial Step for Establishing Cardio-Oncology Service - Farhan, Hasan Ali; Yaseen, Israa Fadhil (Frontiers in Cardiovascular Medicine, 2021)
Background: Over the last years, there was no established cardio-oncology service in Iraq and no firm data about the incidence of cardiovascular disease (CVD) among patients with cancer. As an initial step, we decided to conduct a national cardio-oncology online survey for cardiologists, oncologists, and their residents which would help us to understand the expected prevalence, problems, and readiness for collaboration between the two specialties. Objectives: For evaluating the current national practice in the cardiology and oncology specialty fields and to identify the hidden gaps associated with the development or worsening of CVD among patients with cancer. Methods: An online survey including 19-question for cardiologists/cardiology residents (CCRs) and 30-question for oncologists/oncology residents (OORs) about cardio-oncology service was sent to them including all Iraqi cities using Google document form during December 2020. Results: The total number of responses was 164, mainly 62.2% from CCRs while 37.8% from OORs. Hypertension was the main baseline risk factor (71%). A 77.5% of CCRs prescribe cardiovascular drugs vs. 35.5% by OORs. About 76.5% of CCRs and 79% of OORs are facing difficulties in the management of patients with cancer with established CVD. CVD was the leading cause of both hospitalization (30.7%) and mortality (48.4%). About 62.8% of CCRs and 64.5% of OORs have an interest to work in cardio-oncology service. Conclusion: Based on the perception of cardiologists and oncologists, CVD is the main cause of hospitalization and mortality among patients with cancer. High interest among CCRs and OORs to work in cardio-oncology service. Positive initiatives are available to take the action plan in this emerging field.